Analysis of genome and virulence characteristics of seven invasive non-typhoidal Salmonella (iNTS) - HU Yujie; WANG Wei; XU Xuebin; WANG Yan; CUI Xinnan; XU Jin; LI Fengqin (Zhongguo shipin weisheng zazhi, 2021)
ObjectiveTo investigate the genomic and virulence characteristics of seven invasive non-typhoidal Salmonella (iNTS) isolates.MethodsBased on the collection of seven iNTS strains, whole genome sequencing were performed. The serotypes, genomes and virulence factors were identified, annotated and analyzed according to the comparison of genome data and relevant databases.ResultsAmong the seven tested iNTS isolates, six were monophasic, including one Salmonella Typhimurium and two Salmonella I 4, [5], 12∶i∶-(ST34 type), two Salmonella Enteritidis, one Salmonella Corvallis and one unknown serotype with the antigenic formulae of I 4, [5], 12∶d∶- (ST279 type). No consistent rule was found in genomic components and relevant parameter differences varies much between different serotypes than those of the same serotype from different sources. The distribution of virulence factors (VF) was significantly different among different Salmonella serotypes, but the common VF characteristics in iNTS strains were not found, though Capsule/Immune evasion, toxin, peritrichous_flagella and Salmochelin may be associated with high invasiveness. All tested isolates contained type III and type VI secretion systems. The number of secretion protein, type III for S. Corvallis and type VI for Salmonella I 4, [5], 12∶d∶-was the highest among the seven isolates. Pseudogenization of the secreted effector SseI may exist among some Salmonella serotypes which may contribute to the enhancement of Salmonella invasiveness.ConclusionThe common characteristic differences of virulence factor between iNTS and gastroenteritis NTS were not observed at the moment, and highly invasive pathogenic mechanisms still require further analysis and research at the functional transcriptome and proteomic levels to determine the genetic basis of iNTS occurrence and transmission.